Diarrhoeal pathogens in the stools of children living with HIV in Ibadan, Nigeria - Bejide, Oyeniyi S.; Odebode, Mariam A.; Ogunbosi, Babatunde O.; Adekanmbi, Olukemi; Akande, Kolawole O.; Ilori, Temitope; Ogunleye, Veronica O.; Nwachukwu, Victoria U.; Grey-Areben, Aghogho; Akande, Elizabeth T.; Okeke, Iruka N. (Frontiers in Cellular and Infection Microbiology, 2023)
Diarrhoea can be debilitating, particularly in young children. Few investigations of pathogen aetiology in Africans living with human immunodeficiency virus (HIV) have been performed since antiretrovirals became widely available. Stool specimens of children living with HIV and HIV-uninfected controls with diarrhoea recruited at two hospitals in Ibadan, Nigeria were screened for parasites, bacteria and the presence of occult blood. Following biochemical identification of at least five colonies per specimen, diarrhoeagenic Escherichia coli and Salmonella were confirmed by PCR. Data were line-listed and, where possible, comparisons were made using Fisher’s Exact test. Only 10 children living with HIV were enrolled during the study period and 55 HIV-uninfected children with diarrhoea were included for comparison. The most common pathogens overall were enteroaggregative E. coli (18/65, 27.7%), enteroinvasive E. coli (10/65, 15.4%), Cryptosporidium parvum (8/65, 12.3%) and Cyclospora cayetanensis (7/65, 10.8%). At least one pathogen was detected from seven of ten children living with HIV and 27/55 (49.1%) HIV-uninfected children. Parasite detection was associated with HIV positive status (p = 0.03). Bacterial-parasite pathogen combinations were detected in specimens from four of ten children living with HIV but only 3/55 (5.5%) HIV-uninfected children (p=0.009). Occult blood was detected in stools from five of ten children living with HIV and 7 (12.7%) of HIV-negative children (p = 0.014). Children living with HIV present infrequently to Ibadan health facilities with diarrhoea but their greater propensity for mixed and potentially invasive infections justifies prioritizing their stools for laboratory diagnosis.